UHPLC-ESI-MS/MS analyses for quantification of phenolic compounds of Nepeta nuda subsp. Lydiae - Aras, A.; Bursal, Ercan; Doğru, M. (Open Science Publishers LLP Inc., 2016)
Phenolic compounds of Nepeta nuda subsp. Lydiae leaves were identified by UHPLC-ESI-MS/MS. To the best of our knowledge, phenolic compounds in N. nuda subsp. Lydiae are reported for the first time. Chlorogenic acid, rosmarinic acid and quinic acid, were found to be the most abundant compound in the methanol extract of N. nuda subsp. Lydiae, among the twenty-seven compounds studied by LC-MS/MS. Also, smaller amounts of kaempferol, p-coumaric acid, tr-caffeic acid, apigenin, luteolin and rhamnetin were identified, quantitatively. In conclusion, leaves of N. nuda subsp. Lydiae have high potential of phenolic contents that mainly attributed with biological activities. © 2016 Abdulmelik Aras et al.
Keywords: Chlorogenic acid; Nepeta nuda; Phenolic acid; Quinic acid; Rosmarinic acid